Negative Solvatochromism of an Anionic Thiazole‐Based Dye. Issue 6 (3rd June 2013) - Schade, Alexander; Menzel, Roberto; Görls, Helmar; Spange, Stefan; Beckert, Rainer
<x xml:space="preserve">Abstract</x> Keep it small, flat, and easy: The synthesis of an unconventional strong solvatochromic dye is presented. The solvatochromic and NMR behavior of the anionic chromophore was characterized and the compound might be used as a sensor. The thiazol‐4‐olate donor group is derived from the oxyluciferin of fireflies and strongly influences the electronic properties of the dye.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>